PD-like controller for delayed bilateral teleoperation of wheeled robots. Issue 8 (2nd August 2016) - Slawiñski, E.; Mut, V.; Santiago, D.
ABSTRACT: This paper proposes a proportional derivative (PD)-like controller applied to the delayed bilateral teleoperation of wheeled robots with force feedback in face of asymmetric and varying-time delays. In contrast to bilateral teleoperation of manipulator robots, in these systems, there is a mismatch between the models of the master and slave (mobile robot), problem that is approached in this work, where the system stability is analysed. From this study, it is possible to infer the control parameters, depending on the time delay, necessary to assure stability. Finally, the performance of the delayed teleoperation system is evaluated through tests where a human operator drives a 3D simulator as well as a mobile robot for pushing objects.